Identification of Residues of the Kid Toxin Involved in Autoregulation of the parD System - Lemonnier, Marc (American Society for Microbiology, 2004)
The toxin-antitoxin system parD (kis kid) of plasmid R1 is coregulated by the coordinated action of its two gene products. Here we describe the isolation and the in vivo characterization of three single-amino-acid changes in the Kid toxin, G4E, C74Y, and E91K, that affect the coregulatory activity but preserve the toxicity of the protein.